E-books as self-learning resources for educational technology students - Pratama, Muh. Putra; Adam, Muh. Wahyu Suryandi (Jurnal Kependidikan Media, 2024)
The purpose of this study was to describe the learning outcomes and responses of students of the educational technology study program regarding e-books as a learning resource. In this study using descriptive qualitative as an approach procedure that produces data descriptions in the form of written words that try to describe and interpret what exists or about existing conditions or relationships, developing opinions, and ongoing processes, with data collection techniques by means of observation and questionnaires. The results of the analysis show that students of the education technology study program class of 2020 have used e-books as an independent learning resource based on the results of the analysis conducted. If calculated, almost 100% have used e-books as an independent learning resource, which are accessed via computers, leptops and smartphones. As a learning resource, of course, it is considered capable of providing the information needed by students both in the form of plain text, PDF format, and JPEG. the use of e-books as a source of independent learning for education technology students has its own advantages and disadvantages. However, the percentage shows 90% showing a positive impact. The remaining 10% shows the weaknesses of the e-book.